Math, asked by femypiusallen, 6 months ago

If theSum of the quadratic equation 3x²-kx+6 is 3 Find k

Answers

Answered by Anonymous
39

__________________

➪ In a general quadratic equation of form

ax² + bx + c = 0

➪ the sum of its by -b /4

In the given quadratic equation,

3x² −kx +6 =0

a= 3,b= −k,c = 6

➪sum of the roots = -b/4 = -(-k) /3 = k /3

➪ k /3 = 3

k = 9

____________________________

this is your accurate answer✔︎

Answered by tennetiraj86
5

Answer:

\huge{\boxed{\rm{\red{k=9}}}}

Step-by-step explanation:

Given quadratic equation is 3x²-kx+6=0

On comparing with the standard quadratic equation ax²+bx+c=0 then we have

a=3;

b=-k;

c=6

Given that

the sum of the roots =3

we know that the sum of the roots of ax²+bx+c=0 is -b/a

=>-b/a=3

=>-(-k)/3=3

=>k/3=3

=>k=3×3

=>k=9

The value of k=9

Similar questions